Assessment of body mass index in patients with chronic hepatitis C who received an effective antiviral therapy - Kristina R. Dudina; Petr A. Belyy; Igor V. Maev; Elena A. Klimova; Svetlana A. Shutko; Olga O. Znoyko; Nikolay D. Yuschuk (Терапевтический архив, 2023)
Aim. To evaluate the body mass index (BMI) in patients with chronic hepatitis C (CHC) with different stages of liver fibrosis and steatosis who received effective antiviral therapy (AVT).